Murder by the millions - Gerber, Daryl Wood (Gerber, Daryl Wood. Literary dining mystery series, 2025)
"If it were true that the best thing a girl can be in this world is a fool, then Allie Catt would be out of luck. Fortunately, Allie's business is a smashing success. And following her Pride and Prejudice event, grander plans await . . . Feast for the Eyes bookstore manager and Allie's best friend, Tegan, is hosting a book club soiree and wants it to be a glittering affair based on F. Scott Fitzgerald's iconic Jazz Age-set novel, The Great Gatsby. Soon, Art Deco table settings and visions of flappers are dancing the Charleston in their heads. Even Tegan's prickly sister, Vanna, is on board. And surely,Allie's tuxedo cat, Darcy, thinks it's the cat's meow. Amid the planning, charismatic developer Jason Gardner arrives in town to buy some historic buildings on Main Street. He, too, has plans: to create a modern mall. Allie is more than concerned. She even wants to protest. But when Jason invites her to cater a lavish party, she finds him surprisingly likable. Then she's summoned to his estate for a meeting--and finds him dead. Once again Allie's landed in the middle of a crime scene. Worse, one of her earrings is later discovered near the body. And when police learn she was upset about the mall, she's suspect #1. Allie's blossoming sleuthing skills once cleared Tegan's name, but can she save herself--before a killer writes her a not-so-great Gatsbyesque ending . . ."--